Optimización de la gestión integral de desechos sólidos en el recinto Chipe del cantón Valencia - Zambrano Loor, Jomaira Lisseth (2021)
This research was carried out in the Chipe area, belonging to the canton of Valencia, with the purpose of reducing the sources of contamination generated by inadequate solid waste management and also to promote environmental culture and awareness among the citizens. The study is based on a diagnosis of the current situation of solid waste management in the sector, which was carried out through surveys and technical inspections of the residents, as well as interviews with the president of the sector and the municipal staff in charge of public sanitation, in order to know their perception of the current situation of the area. A total of 54 samples were taken, distributed between 11 de junio and José Plúa streets, for the characterization of solid waste in each household, obtaining a per capita generation of o.28 kg, i.e. daily waste production of 0.266 kg/hab/day, and an MSW composition of organic waste (69%), plastics (16%), sanitary waste (10%), paper/cardboard (3%) and in smaller quantities glass and metal (1%). With the results obtained, a manual was designed that includes topics such as waste conceptualization, waste characterization, integral management of household waste (generation, storage, collection, type and number of containers for collection and final disposal), so that citizens have a guide for the proper management of their solid waste. KEY WORDS: Integrated solid waste management, inadequate waste management, environmental diagnosis, waste classification, waste management manual.